2006
DOI: 10.1007/11802914_5
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Accuracy Analysis for Discrete Surface Approximation

Abstract: In geometric modeling and processing, computer graphics and computer vision, smooth surfaces are approximated by discrete triangular meshes reconstructed from sample points on the surfaces. A fundamental problem is to design rigorous algorithms to guarantee the geometric approximation accuracy by controlling the sampling density. This paper gives explicit formulae to the bounds of Hausdorff distance, normal distance and Riemannian metric distortion between the smooth surface and the discrete mesh in terms of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…However, we have not demonstrated that the new sampling conditions are sufficient to ensure that the iDt‐mesh is a substructure of the 3D Delaunay tetrahedralization. Since good convergence properties of the iDt‐mesh have been demonstrated [DLYG06], this would put it on a more or less equal footing with the rDt. It is known that the rDt and the iDt‐mesh are not necessarily combinatorially equivalent, regardless of sampling density [DZM07].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have not demonstrated that the new sampling conditions are sufficient to ensure that the iDt‐mesh is a substructure of the 3D Delaunay tetrahedralization. Since good convergence properties of the iDt‐mesh have been demonstrated [DLYG06], this would put it on a more or less equal footing with the rDt. It is known that the rDt and the iDt‐mesh are not necessarily combinatorially equivalent, regardless of sampling density [DZM07].…”
Section: Discussionmentioning
confidence: 99%
“…Although our work focuses more on the qualitative local behaviour of geodesics, we did exploit these works when it was necessary to bound geodesic lengths to allow a comparison between intrinsic and extrinsic sampling criteria. Dai et al [DLYG06] have also recently produced a geometric accuracy analysis. Their analysis is from the intrinsic viewpoint, using Leibon and Letscher's work [LL00] as the topological correctness foundation.…”
Section: Introductionmentioning
confidence: 99%
“…The concepts of conformal maps, hyperbolic metrics and Ricci flow are also translated from the smooth surface category to the discrete mesh category. We show the Riemannian metrics of meshes induced by Delaunay triangulations converge to the metric on the smooth surface in [Dai et al 2006]. The convergence of conformal structures is proved in [Luo 2006].…”
Section: Hyperbolic Discrete Variational Ricci Flowmentioning
confidence: 98%
“…Under the assumption of convergence of surfaces in Hausdorff distance, Hildebrandt et al [12] proved that convergence of the following properties are equivalent: surface normals, surface area, metric tensors, and Laplace Beltrami operators. Dai et al [7] derived the explicit formulae to the bounds of Hausdorff distance, normal distance, and Riemannian metric distortion between the smooth surface and the triangle mesh. They proved that the meshes induced from Delaunay triangulations of dense samples on a smooth surface are convergent to the smooth surface under both Hausdorff distance and normal fields.…”
Section: Related Workmentioning
confidence: 99%